A NOVEL MATHEMATICAL MODEL OF AIRBORNE INFECTION - Nur Intan Syafinaz Ahmad; Aishah Mahat; Ahmad Khudzairi Khalid; Nurhuda Ismail; Muhammad Syawal Abd Halim, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2019)
: Every person can't see how infection through air will transfer from one person to other person. Those who're doing outdoor activities, they will be more exposed to many infections. Due to every infection can't be seen by eyes, most people will be ignoring the way how to prevent themselves from viruses via airborne transmission in public area especially using public transport. This paper focus to airborne transmission in train. This research used Wells-Riley Model because it is suitable for small population in a closed space. This model has been widely used for quantifying the infection risk assessment of respiratory infectious diseases indoor place. The risk of secondary infection is under control when the exposure time is less than 30 minutes for 150 passengers or less than one hour for 75 passengers and the reproduction number is estimated at 0.03. However, the reproduction number of second infections, Q A is fairly insensitive to the number of passengers as the exposure time increase. But it is still under the skill of epidemic control as if Q A is under 0.03. So, the spread of epidemic can be control. If Q A more than 0.03 then procedures of prevention should be done.